A prospective single centre study comparing computed tomography pneumocolon against colonoscopy in the detection of colorectal neoplasms. Issue 6 (1st December 2000) - Miao, Y M; Amin, Z; Healy, J; Burn, P; Murugan, N; Westaby, D; Allen-Mersh, T G
Abstract : BACKGROUND AND AIMS: To determine the sensitivity and specificity of computed tomography (CT) pneumocolon in the detection of colorectal neoplasms. METHODS: A total of 201 consecutive patients with colorectal symptoms or requiring surveillance for colorectal neoplasms underwent both conventional colonoscopy and CT pneumocolon. RESULTS: On conventional colonoscopy 13 invasive colorectal carcinomas were detected in 13 patients, and 118 polyps in 63 patients (14 polyps were ⩾1 cm in diameter, 25 were 6–9 mm, and 79 were ⩽5 mm). CT pneumocolon detected all 13 cancers, two false positive cancers, but only 20 polyps (seven were ⩾1 cm). This resulted in a sensitivity of 100% (95% confidence interval (CI) 87–100%) and specificity of 99% (95% CI 97–100%) for detection of invasive carcinoma, and a sensitivity of 73% (95% CI 56–90%) and specificity of 94% (95% CI 91–98%) for detection of invasive carcinoma and/or ⩾1 cm polyps. CT pneumocolon also identified invasive carcinoma not seen at colonoscopy because of incomplete examination in three patients, and detected metastases in six colorectal carcinoma patients and extracolonic carcinoma in a further seven patients. CONCLUSIONS: CT pneumocolon had a high sensitivity and specificity for detection of invasive colorectal carcinoma but not colorectal polyps. CT pneumocolon may be suitable for initial investigation of patients with symptoms of colorectal malignancy.